Effect of cations on the removal rate of chloride ions and mechanism analysis in high-salt wastewater - Kangning Gao (IWA Publishing, 2021)
Precipitation dechlorination has the advantage of being a simple process with a low cost. However, there are few reports on the effect of cations on dechlorination. In this study, we investigated the effect of cations in high-salt wastewater on the removal of chlorine ions by cuprous chloride precipitation and analysed the corresponding mechanism. A series of investigations revealed that Fe3+ could oxidise sulphite, thereby reducing the removal rate of chlorine ions. The reaction between magnesium and sulphite results in precipitation, which has a slightly adverse effect on the removal of chloride ions. Hexavalent chromium oxidises the chloride ion, resulting in the formation of chlorine gas, which improves the removal rate. Ferrous and manganese, however, do not have a notable effect on chlorine removal. HIGHLIGHTS This paper describes the effect of cations in high-salt wastewater on the removal of chlorine ions by cuprous chloride precipitation.; Fe3+ can be converted to Fe2+ to reduce the inhibitory effect on chloride ion removal.; Chromium oxidises the chloride ion, which improves the removal rate.; The removal of chloride ions from high-salt wastewater via the cuprous chloride precipitation method is economical.;